2024
DOI: 10.4093/dmj.2023.0301
|View full text |Cite
|
Sign up to set email alerts
|

Does the Relationship of the Autonomic Symptoms Questionnaire COMPASS 31 with Cardiovascular Autonomic Tests Differ between Type 1 and Type 2 Diabetes Mellitus?

Ilenia D’Ippolito,
Marika Menduni,
Cinzia D’Amato
et al.

Abstract: Background:The aim was to investigate if autonomic symptoms questionnaire Composite Autonomic Symptom Score (COM-PASS) 31 has different association with cardiovascular autonomic neuropathy (CAN) and diagnostic performance between type 1 diabetes mellitus (T1DM) and type 2 diabetes mellitus (T2DM). Methods: Seventy-nine participants with T1DM and 140 with T2DM completed COMPASS 31 before cardiovascular reflex tests (CARTs) for CAN, and assessment of symptoms, signs, vibration, and thermal perception thresholds … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…Similarly, earlier studies on patients with diabetes showed an overall weak correlation between CASS scores and autonomic symptoms using the Autonomic Symptom Profile questionnaire ( Low et al, 2004 ). In another study ( D’Ippolito et al, 2024 ), COMPASS-31 exhibited a weak association with CAN in type 1 diabetes mellitus and type 2 diabetes mellitus indicating a multifactorial origin of symptoms. In our study, patient-reported autonomic symptoms (total COMPASS-31 score and OI score) were correlated with hemodynamic changes (ΔBP and ΔTPR) induced by AFTs.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Similarly, earlier studies on patients with diabetes showed an overall weak correlation between CASS scores and autonomic symptoms using the Autonomic Symptom Profile questionnaire ( Low et al, 2004 ). In another study ( D’Ippolito et al, 2024 ), COMPASS-31 exhibited a weak association with CAN in type 1 diabetes mellitus and type 2 diabetes mellitus indicating a multifactorial origin of symptoms. In our study, patient-reported autonomic symptoms (total COMPASS-31 score and OI score) were correlated with hemodynamic changes (ΔBP and ΔTPR) induced by AFTs.…”
Section: Discussionmentioning
confidence: 91%
“…There are conflicting findings regarding the relationship between autonomic questionnaires and autonomic function tests (AFTs) or CASS. Studies have shown a lack of or weak correlations in diabetic and mixed neurological patient groups ( Low et al, 2004 ; D’Ippolito et al, 2024 ; Novak et al, 2024 ). Currently, there is a scarcity of comprehensive assessments of the prevalence and severity of autonomic dysfunction in MG, including subjective and objective measures as well as investigating its relationship with disease outcomes.…”
Section: Introductionmentioning
confidence: 99%